Developing professional digital competence in Norwegian teacher education: a scoping review - Norhagen, Sigrun Lindaas; Krumsvik, Rune Johan; Røkenes, Fredrik Mørk (Frontiers in Education, 2024)
The widespread use of educational technology in schools compels teachers to seamlessly integrate technology while developing students' digital competence. As educational technology continually evolves, digital competence becomes a dynamic target. Thus, teacher education must effectively prepare student teachers to teach effectively with technology. Researchers are increasingly examining the concept of teachers' digital competence and how teacher education supports student teachers' acquisition of digital skills for future employability. In Nordic countries like Norway, the term Professional Digital Competence (PDC) frames a teacher's essential knowledge for using digital technology in teaching and learning. Despite this focus, there's limited understanding of how Norwegian teacher education fosters PDC. This scoping review investigates current research on PDC and its implementation within Norwegian teacher education. Findings from numerical and thematic analysis offer insights into the prevalent types of PDC research. Thirty-four peer-reviewed papers were identified and coded along three dimensions: (1) theoretical perspectives, (2) research questions and methods, and (3) application and implementation. The review reveals a predominant focus on student and teacher educator perceptions or self-ratings of their digital competence, teacher educators' digital abilities, or the adequacy of programs in facilitating digital competence. Implications for teacher education are discussed.